2018
DOI: 10.3389/fmicb.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Comparative Proteomic Analysis of Adult Schistosoma japonicum from Water Buffalo and Yellow Cattle

Abstract: Schistosomiasis japonicum is one of the most severe zoonotic diseases in China. Water buffalo and yellow cattle are important reservoir hosts and the main transmission sources of Schistosoma japonicum in endemic areas. The susceptibility of these two hosts to schistosome infection is different, as water buffaloes are less susceptible to S. japonicum than yellow cattle. In this study, iTRAQ-coupled LC-MS/MS was applied to compare the protein expression profiles of adult schistosomes recovered from water buffalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Reactive oxygen species are found in normal living organisms where they are constantly being produced under the oxidative stress caused by toxic heavy metals, heat shock, inflammation, ionizing irradiation, immune responses, and environmental stimuli ( Zhai et al, 2018 ). Studies have shown that antioxidant enzymes can remove and reduce ROS produced by metabolic stress conditions in an attempt to maintain homeostatic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species are found in normal living organisms where they are constantly being produced under the oxidative stress caused by toxic heavy metals, heat shock, inflammation, ionizing irradiation, immune responses, and environmental stimuli ( Zhai et al, 2018 ). Studies have shown that antioxidant enzymes can remove and reduce ROS produced by metabolic stress conditions in an attempt to maintain homeostatic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic initiation factor 4A is a highly conserved RNA-stimulated ATPase and helicase involved in the initiation of mRNA translation, which has been found to play an important role in ovule development and cell size homeostasis in Arabidopsis [77]. However, the available information was limited to make further correlation analysis between differentially expressed miRNAs and the differentially expressed proteins of worms derived from yellow cattle and water buffalo [16]. A total of 131 differentially expressed proteins were identified between worms from yellow cattle and water buffalo in our previous study, but only 49 differentially expressed proteins were annotated in the known database [16].…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification was performed with a SYBR ® PremixEx Taq™ kit (TaKaRa, Dalian, China) on an ABI 7500 Real-Time System (Applied Biosystems). The reaction conditions were as follows: 95 °C for 30 s, 40 cycles of 95 °C for 5 s and 60 °C for 34 s. Sj NADH was selected as an internal reference [16]. The target gene numbers and primer sequences are shown in Additional file 4: Table S3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers had endeavored to explore the genes participating or involved in the regulation of the development and reproductive maturation of schistosomes by comparative transcriptome, proteome, and metabolome research and gained great discoveries in the growth and reproductive biology of schistosomes (Gupta and Basch, 1987;Haseeb et al, 1989;Siegel and Tracy, 1989;Haseeb and Eveland, 1991;Grevelding et al, 1997;Haseeb, 1998;Liu et al, 2006;Cogswell et al, 2012;Leutner et al, 2013;Protasio et al, 2013;Sun et al, 2014;Han et al, 2015a,b;Cao et al, 2016;Picard et al, 2016;Zhai et al, 2018;Li et al, 2019;Mao et al, 2019). Recently, we have also investigated and reported the differential metabolomic profiles of S. japonicum parasites from SCID and BALB/c mice in order to explore the molecular events involved in the aberrant morphologies in the growth and reproduction of schistosomes from a metabolomic level.…”
mentioning
confidence: 99%